Composition of semi-volatile organic compounds in the urban atmosphere of Singapore: influence of biomass burning - He, J.; Zielinska, B.; Balasubramanian, R. (European Geosciences Union (EGU), 2010)
An intensive field study was conducted in the urban atmosphere of Singapore to investigate the composition of organic compounds in both gaseous and particulate phases during the period of August to early November 2006. 17 atmospheric samples were collected. These samples were subjected to accelerated solvent extraction with a mixture of dichloromethane and acetone and separated into functional group fractions for analyses by GC/MS. Over 180 organic compounds belonging to three major fractions (n-alkanes, polycyclic aromatic hydrocarbons – PAHs, and polar organic compounds – POCs) were identified and quantified. The characteristics and abundance of the n-alkanes, PAHs, mono and dicarboxylic acids, methoxylated phenols and other POCs were determined. The composition of these organic compounds fluctuated temporally with most of them being relatively higher in October than those in other months of the sampling period. 3-D backward air mass trajectory analyses together with the carbon preference index (CPI), molecular diagnostic ratios and molecular markers were used to investigate the origin of organic species measured in this study. Based on these diagnostic tools, the increased abundance of atmospheric organic species during October could be attributed to the occurrence of regional smoke haze episodes due to biomass burning in Indonesia. Among the POCs investigated, phthalic acid and cis-pinonic acid were abundant during October 2006. These two acids showed strong linear relationships with maximum daily ozone concentrations throughout the entire sampling period. This correlation with ozone suggested that the secondary aerosol constituents such as phthalic and cis-pinonic acids were probably formed through O3-induced photochemical transformation.